Lifetime and degradation of high temperature PEM membrane electrode assemblies. (14th December 2015) - Kerr, R.; García, H.R.; Rastedt, M.; Wagner, P.; Alfaro, S.M.; Romero, M.T.; Terkelsen, C.; Steenberg, T.; Hjuler, H.A.
Abstract: This work will provide details on some of the high temperature polymer electrolyte membrane (HTPEM) membrane-electrode-assembly (MEA) performance targets most recently achieved by Danish Power Systems. These include (i) MEA performances of >0.67 V at 0.2 A cm −2 using dry H2 /Air, (ii) MEA lifetime of 17.000 h at 0.24 A cm −2 using dry H2 /Air with an average degradation rate of 9 μV h −1, and (iii) an integrated 5 kW stack/reformer system using methanol reformate as fuel. Post mortem SEM, TEM, micro-tomography and XRD showed membrane thinning and catalyst particle growth that is typical for PEM fuel cells. Platinum particles grew from an initial 2–3 nm to 6–8 nm at the cathode and 4–5 nm at the anode, while the membrane showed thinning from an undoped 40 μm–18 μm in some areas after testing. Studies using reformate have also led to promising initial results, while the rate of degradation for an MEA supplied with wet H2 (30 mol%)/Air for 2000 h was found to be very similar to the rate when supplied with dry H2 . In addition to reaching these performance benchmarks, a reduction in the standard deviation for MEA cell voltage at 0.2 A cm −2 to <1% has been achieved through efforts aimed at improving the uniformity of the membrane and catalyst layer thicknesses.